Características do pelame de cabras saanen e pardo alpina criadas em ambiente tropical - Aiura, A. L. O.; Aiura, F. S.; Silva, R. G. [UNESP] (SciELO Espana/Repisalud, 2010)
The aim of the present work was to study the morphological characteristics of the hair coat, coat thickness (E), hair length (C), number of hair by unit area (N), hair angle to skin (A) and hair diameter (D) of Saanen and Oberhasli goats, measured under the conditions of tropical environment. The observed averages of these traits were: E= 6.04±0.08 mm; C= 33.17±0.24 mm; N= 191.50±4.67 hairs.cm-2; A= the 10.67±0.15 degrees; D= 0.203±0.0013 mm.
Hair coat characteristics of saanen and oberhasli goats in tropical environments
Keywords: Adaptation; Goats; Heat load; Capra hircus